PENGARUH MOTIVASI, PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA PEGAWAI DI KANTOR CAMAT MUARA PAHU KABUPATEN KUTAI BARAT - -, Ali Rachman (EKONOMIA, 2014)
Through this training followed a government apparatus will have an underlying act of professional competence in the work environment or their respective organizations. Competence under Indonesian Government Regulation No. 101 of 2000 on Education and Job Training Civil Servants are the capabilities and characteristics possessed by a Civil Servant in the form of knowledge, skills, and attitude-behavior required in the execution of their office. The motivation and with the opportunity given to an employee in the following Training will hopefully encourage performance that will eventually give birth to a reliable and outstanding employees. Motivation will result in positive behavior of employees in creating achievement. By following Training is expected to be a provision for an employee to perform new innovations and generating performance. In other words, that the achievement would not have materialized without the motivation and the ability to produce it.The aim of the research is: 1) Determine the influence of motivation, education and training on the performance of employees at Head Office Muara Pahu West Kutai. 2) Determine the influence of motivation on the performance of employees at Head Office Muara Pahu West Kutai. 3) Determine the influence of education and training on the performance of employees at Head Office Muara Pahu Kutai Barat.Peneitian was conducted on employees in the Office of Muara Pahu district. Samples were selected by census as many as 33 respondents, according to the number of Civil Servants in the study area. The collected data will be analyzed using Statistical Parametric test equipment by using Multiple Regression, in this case would be helped by using SPSS version 20 (Statistical Program for Social Science).The results of the study showed that: 1) Motivation, education and training jointly insignificant effect on the performance of employees at Head Office Muara Pahu West Kutai. 2) Motivation no significant effect on the performance of employees at Head Office Muara Pahu West Kutai. 3) Education and training did not significantly affect the performance of the employees in aterhadap Head Office Muara Pahu Kutai Barat.